Trade liberalisation, prices and the skill premium in South Africa - Mashiane, Jeffrey (School of Economics, 2014)
We look at how trade liberalisation, working through product prices, has affected the skill premium in South Africa over the period 1990-2009. Our main finding is that trade liberalisation lead to a reduction in prices over this period, and through prices mandated a rise in the skill premium of 3.3%. The structure of the skill premium did not stay constant over the period. In the sub-period 1990-1999, trade liberalisation mandated a fall in the skill premium of 10.6% and in the other sub-period 2000-2009, trade liberalisation mandated a rise in the skill premium of 11.6%. Our main results are consistent with the sector bias of tariff cuts over these periods, however they do not pass some of the robustness checks that we perform.